Odd man out: why are there fewer plant species in African rain forests? - (:unkn) unknown (My University, 2015)
Although tropical rain forests represent the most species-rich terrestrial ecosystem on the planet, the three main rain forest regions (Neotropics, South-East Asia and continental Africa) are not equally diverse. Africa has been labeled the “odd man out” because of its perceived lower species diversity when compared to the Neotropics or South-East Asia. Understanding why, within a biome, certain regions have higher or lower species diversity provides important insights into the evolution of biodiversity. I review the evidence in favor of an “odd man out” pattern and the different hypotheses that have been advanced to explain and test this pattern using recent ecological, biogeographical and diversification studies. The “odd man out” pattern has yet to be formally tested using extensive inventory plot data (including non woody species) between all three major rain forest regions based on appropriate statistics in an area controlled manner. The lower species diversity is not the result of a single cause, but is probably linked to numerous intricate causes related to present and past events. Future comparative studies should combine numerous variables including novel ones such at plant functional diversity. Finally, though more extinction in Africa is apparent from the fossil record, it is still hard to precisely quantify to what degree extinction varied between the three major regions. Diversification studies of important tropical plant lineages tend to support higher speciation rates in the Neotropics and South-East Asia instead of higher extinction in Africa as the main cause explaining the differences in species diversity. The lower species diversity of African rain forests remains an understudied question with numerous preconceived and largely untested ideas for which we are still far from having a synthetic explanation. This review highlights that there are still very little intercontinental rain forest comparisons of plant species diver
Keywords: African Research